Connecting the Dots: Structural Racism, Intersectionality, and Cardiovascular Health Outcomes for African, Caribbean, and Black Mothers (Mary Ann Liebert, 2022)
African, Caribbean, and Black (ACB) women globally experience health inequities that impact on their cardiovascular health outcomes during the perinatal period, and for years after. Aside from being at a high risk of having and dying from hypertensive disorders of pregnancy, ACB women who survive face a lifelong risk of cardiovascular disease years after the diagnosis. Racism as a determinant of health intersects with gender, societal structures, and immigration status to contribute to cardiovascular health and access to quality health care services for ACB women. Equitable policies and culturally appropriate programs are needed to improve the cardiovascular health of ACB women.